Hydrothermal synthesis of a nickel-oxide-infused orange peel nanobiocomposite for enhanced heavy metal removal from mining wastewater - Jacques Romain Njimou; Velma Fai; Mary Tamwa Sieugaing; Djimongbaye Nguenamadje; John Godwin; Oben Bessem Genola; Guy Bertrand Noumi; Bankim Chandra Tripathy (Hybrid Advances)
Heavy metals in various geochemical forms, such as exchangeable ions, carbonates, and oxides, pose significant risks to human health and the environment due to their persistence and bioaccumulation. Their mobility and toxicity depend on their chemical states, many of which are toxic, mutagenic, or carcinogenic. This study presents an innovative nanobiocomposite synthesized via hydrothermal methods, combining nickel oxide (NiO) and orange peel (OP) with alginate to create nickel-orange peel beads (Alg/OP-Ni). These beads exhibit exceptional adsorption capabilities for removing cadmium (Cd2⁺) and lead (Pb2⁺) ions, outperforming conventional materials. Characterization techniques such as FTIR, XRD, SEM, and EDS reveal a highly porous morphology due to NiO nanoparticle integration within the OP matrix, a structure that provides numerous active sites for adsorption. This innovative approach leverages agricultural waste, turning orange peels into a high-performance, eco-friendly adsorbent, thereby addressing both environmental pollution and waste management challenges.Co-adsorption of Cd2⁺ and Pb2⁺ ions was investigated, focusing on pH, biomass dosage, contact time, initial concentration, and temperature. Adsorption data were modeled using Langmuir, Freundlich, and Dubinin-Radushkevich isotherms, indicating monolayer adsorption consistent with the Langmuir model. The adsorption mechanism involves a two-step process where positively charged Cd2⁺ and Pb2⁺ ions diffuse toward the negatively charged surface of the Alg-OP-Ni nanobiocomposite and subsequently fix through interactions with surface oxygen atoms. Maximum adsorption capacities for Cd2⁺ and Pb2⁺ were determined to be 138.25 and 276.00 mg/g in single-component systems, and 224.00 and 317.10 mg/g in binary systems, respectively. Kinetic studies suggest a pseudo-second-order model for the adsorption process. Tests with river water samples from Bétaré-Oya, Cameroon, confirm effective heavy metal removal, indicating the Alg/OP-Ni nanocomposite's potential as a sustainable solution for mining wastewater remediation. This study not only demonstrates the feasibility of using agricultural waste to create high-performance adsorbents but also highlights the significant advancements in adsorption technology for environmental remediation.